2012
DOI: 10.4269/ajtmh.2012.11-0733
|View full text |Cite
|
Sign up to set email alerts
|

Increased Use of Community Medicine Distributors and Rational Use of Drugs in Children Less than Five Years of Age in Uganda Caused by Integrated Community Case Management of Fever

Abstract: We compared use of community medicine distributors (CMDs) and drug use under integrated community case management and home-based management strategies in children 6–59 months of age in eastern Uganda. A cross-sectional study with 1,095 children was nested in a cluster randomized trial with integrated community case management (CMDs treating malaria and pneumonia) as the intervention and home-based management (CMDs treating only malaria) as the control. Care-seeking from CMDs was higher in intervention areas (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 22 publications
3
22
5
Order By: Relevance
“…20 In a multi-methods Ethiopian study, volunteer CHWs treating diarrhoea, pneumonia, and fever and were highly accessed by community members 22 . Our study is complimentary suggesting multi-illness iCCM using CHWs with variable formal education is feasible, which is supportive of work in Eastern Uganda 23,[27][28][29][30] ; however, caution is needed to further understand quality of work, an issue highlighted by a recent study from Central Uganda. 38 A strength of this implementation study was existing government health structure integration, which demonstrated real-life iCCM-programming feasibility and outcomes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…20 In a multi-methods Ethiopian study, volunteer CHWs treating diarrhoea, pneumonia, and fever and were highly accessed by community members 22 . Our study is complimentary suggesting multi-illness iCCM using CHWs with variable formal education is feasible, which is supportive of work in Eastern Uganda 23,[27][28][29][30] ; however, caution is needed to further understand quality of work, an issue highlighted by a recent study from Central Uganda. 38 A strength of this implementation study was existing government health structure integration, which demonstrated real-life iCCM-programming feasibility and outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…'Best practise' evidence on training, monitoring, and evaluation is urgently needed. Although several iCCM study projects are underway, only one group from Eastern Uganda has published intervention outcomes and operational data thus far, specifically demonstrating feasible CHW management using a dual illness algorithm, 27 an increase in care-seeking by rural families with access to iCCM, 28 a sustained quality of care by CHWs using iCCM compared to single-illness management, 29 a sustained adherence to dual illness medicines by families under iCCM compared to single illness treatments, 30 and an increase in prompt and appropriate treatment of pneumonia under iCCM. 23 Healthy Child Uganda (HCU) is a Ugandan-Canadian university partnership that has developed, implemented, and evaluated community-based maternal and child health initiatives involving volunteer CHWs for over a decade.…”
Section: Introductionmentioning
confidence: 99%
“…The 2009 survey was powered to establish prevalence of pneumococcal carriage rates. In the cRCT, community health workers (CHWs) were trained and equipped to provide community case management of malaria (control) or malaria and pneumonia (intervention) for children aged 6–59 months [25]. Data on antibiotic resistance from these surveys is presented elsewhere [26].…”
Section: Methodsmentioning
confidence: 99%
“…For the survey in 2009, the sample size calculations were set to estimate the true prevalence of children carrying pneumococci and the assumptions used were p equal to 50%, 5% margin of error, and a cluster effect of 1.7 was added, yielding a total number of 650 children to be swabbed for bacteria. For the 2011 study, the sample size calculations of the cluster randomised trial were presented in the paper by Kalyango et al [25] which generated a total sample of 1400 children under five after assuming a 25% non-response rate. Assumptions in 2011 used were 5% level of significance, 80% power, design effect of 1.9, 54% of children ill in previous 2 weeks, and a change in proportion of children receiving prompt and appropriate treatment of malaria from before the intervention (7.4–13.5%), giving a change rate of 13.5–24.3%, yielding a total number of 1094 children to be swabbed for bacteria.…”
Section: Methodsmentioning
confidence: 99%
“…The patronage of community drug distributors has been encouraging and their performance has improved malaria case management at the community level and contributed to lessening the severity and mortality due to malaria [9,10]. CBAs are voluntary workers and to sustain their spirit of volunteerism good incentive of motivation packages are essential.…”
Section: Introductionmentioning
confidence: 99%